2014
DOI: 10.1103/physreva.89.035802
|View full text |Cite
|
Sign up to set email alerts
|

Reexamination of conservation of momentum and energy in partially coherent electromagnetic waves

Abstract: We reviewed the conservation of momentum and energy in partially coherent electromagnetic wave fields in a unified perspective. We find that there is interference between the radiation from polarization and magnetization sources in the momentum flow unlike the result proposed in the previous study. The interference effect can be probed in an example by observing the angular distribution.There has been significant progress in basic conservation relations in partially coherent wave fields recently [1-4] after fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The entangled state concept has been addressed in many papers and some books [38][39][40][41][42][43][44][45][46][47][48][49] over the past two decades, but it has not been used to discuss the conservation of P. Some recent papers [25][26][27][28][29][30][31] have discussed the law of the conservation of P without considering the concept of an entangled state.…”
Section: Entangled States and The Law Of Conservation Of Momentummentioning
confidence: 99%
See 1 more Smart Citation
“…The entangled state concept has been addressed in many papers and some books [38][39][40][41][42][43][44][45][46][47][48][49] over the past two decades, but it has not been used to discuss the conservation of P. Some recent papers [25][26][27][28][29][30][31] have discussed the law of the conservation of P without considering the concept of an entangled state.…”
Section: Entangled States and The Law Of Conservation Of Momentummentioning
confidence: 99%
“…The neutron was discovered [19] and some experimental phenomena [20,21] were explained using the strict laws. Some authors [22][23][24][25][26][27][28][29][30][31] have suggested that the conservation laws are strict and have applied the laws in theoretical analyses. Different from many books, only Zeng's books [37,38] wrote about the strict conservation in the single processes.…”
Section: Introductionmentioning
confidence: 99%